Bacterial flora of mud crab, Scylla olivacea, collected from different markets of Dhaka City (Bangladesh Journal of Zoology, 2015)
The present study was carried out to investigate the bacterial flora of mud crab (Scylla olivacea) meat collected from the five markets of Dhaka city. Faecal Coliform, Salmonella sp. and Shigella sp., E. coil, and Vibrio spp. were detected in most of the samples except the frozen ones from Agora super shop. The samples from Basabo and Karwan bazar had higher bacterial load than the others. The highest TBC counts were observed in the samples from Karwan bazar (38.1 ± 1.20 x 104cfu/g) and the lowest were from Agora super shop (4.48 ± 0.26 x104cfu/g). The total Vibrio spp. counts were found only in two markets, i.e. from Farmgate and Basabo. The total E. coli counts ranged from 1.25 ± 0.02 x 104cfu/g to 4.33 ± 0.56 x 104cfu/g. The Salmonella and Shigella counts varied between3.95 ± 0.28 x 104cfu/g for Karwan bazaar and 16.76 ± 1.26 x 104cfu/g for Basabo. Total Staphylococcus spp. counts ranged between 14.4 ± 1.1 x 104cfu/g and 20.01± 1.94 x 104cfu/g for normal crab samples and 0.37 ± 0.025 x 104cfu/g for frozen samples. The results of this study showed that the bacterial load was significantly higher in live crab than the frozen crab indicating that later are safe for human consumption.Bangladesh J. Zool. 43(1): 55-62, 2015